Adaptive Dynamic Surface Control of MEMS Gyroscope Sensor Using Fuzzy Compensator - Dandan Lei; Tengteng Wang; Di Cao; Juntao Fei (IEEE Access, 2016)
A novel adaptive method for the micro-electro mechanical systems (MEMSs) gyroscope based on a dynamic surface control and combined with the approach of adaptive fuzzy and sliding mode control (SMC) was shown in this paper. The first-order filter was introduced to the conventional adaptive backstepping technique in the dynamic surface control, which not only maintains the advantage of original backstepping technique, but also reduces the number of parameters and avoids the problem of parameter expansion. The adaptive fuzzy logic system is employed to approximate the dynamic characteristics of the gyroscope; the SMC is a kind of compensation for the error of the fuzzy approximation, which reduced the chattering phenomenon in adaptive control significantly. The proposed control scheme has improved the dynamic characteristics of the gyroscope, reducing the chattering of inputs and improving the timeliness and effectiveness of tracking. Simulation results indicate that the proposed control scheme has superior performance compared with conventional SMC.